Analisis Nilai Moderasi Beragama pada Serial Nussa dan Rara serta Relevansinya dengan Pembelajaran Agama Islam Kelas IV Sekolah Dasar - Fitama, Diko Nasrul; Andrian, Firma; Annisah, Siti; Adiwijaya, Satria Nugraha; Wibowo, Rahmad Ari (Tapis: Jurnal Penelitian Ilmiah, 2024)
Indonesia's diversity is the main cause of social conflict both verbally and psychologically. Social conflicts that occur in everyday life can certainly bring Indonesia into the abyss of misery. So religious moderation education needs to be integrated into education. The implementation of religious moderation education at an early age, especially in elementary school, is the basic foundation for creating a sense of unity and integrity in Indonesia. This research aims to analyze the values of religious moderation in the Nussa and Rara series and their relevance to Islamic religious learning. This research method uses a literature study, with data collection techniques reviewing documents on the Nussa and Rara video series. The data analysis technique in this research uses detailed qualitative descriptions in the Nussa and Rara video series. The findings in this research show that the value of national commitment is found in the episode "Freedom!!!", the value of tolerance is found in the episode "Tolerance and my neighbor is great", the value of anti-violence is found in the episode "free reward and anger" and the value of accommodating towards local culture is found in the episode "washing hands" Come on! and clean our city, clean Indonesia. The value of religious moderation which includes the value of tolerance, the value of non-violence, and accommodating to local culture turns out to have relevance to Islamic religious learning in grade IV elementary school, while the value of national commitment has no relevance at all.